The Design Of Academic Integration In Indonesia: A Case Study At State-Owned Islamic University Of North Sumatra - Halimah, Siti; Salminawati, Salminawati; Dahlan, Zaini (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Various researches themed on curriculum or academic integration studies find a middle point, that each institution is unique in designing academic integration as a guide to the learning process, including the higher education level. For this reason, this study aims to reveal in depth the focus of academic integration design related to strategies and development models based on the vision and mission of the institution, as well as the locus at UIN North Sumatra Medan and UIN Sheikh Ali Hasan Ahmad Addary Padangsidimpuan. The research method used is a multisite qualitative-interactive approach. The results of this study found that first, the design of academic integration at UIN North Sumatera uses the concept of wahdatul 'ulum. This scientific paradigm is designed starting from the review process, revision, to carrying out curriculum workshops and RPS based on Wahdatul 'Ulum as a concept and practical application. Second, UIN Sheikh Ali Hasan Ahmad Addary Padangsidimpuan uses the concept of Theoanthropoecocentric scientific paradigm based on the Science pyramid. The development of the scientific concept is developed in 7 aspects, including lecturer resources, lecturer activities, teaching systems and curricular programs, recruitment of prospective students, providing an integrative environment, facilities and infrastructure, and strengthening integration in postgraduate programs.